The gangters' God - Public Television Service (Taiwan : Public Television Service, 2006)
Each yar Lantern FEstival in eastern Taiwan, a ritual takes place in which men stand on a sacred palanquin dressed in nothing but red shorts, ahile people pound their bodies with firecrackers that singe their skin. For the duration of the ritual, these man are believed to be invested with the spirit of the god Handan. The ritual known as the Scorching of Handan has become a major event in recent years. The people who take part have always been shrouded in mystery and rumored to be members of the gangaters' underworld
DVD Format
Subtitles in Tradisional Chinese, English, Francais and Espanol
Keywords: Rites and ceremonies -- China